Impact of Different Sampling Strategies on Score Results of the Nine Equivalents of Nursing Manpower Use Score (NEMS) - Junger, A.; Hartmann, B.; Klasen, J.; Brenck, F.; Röhrig, R.; Hempelmann, G. (Methods of Information in Medicine, 2007)
Objective: Prospective observational study to assess the impact of two differentsampling strategies on the score results of the NEMS, used widely to estimate the amount of nursing workload in an ICU.Methods: NEMS scores of all patients admitted to the surgical ICU over a one-year period were automatically calculated twice a day with a patient data management system for each patient day on ICU using two differentsampling strategies (NEMSindividual: 24-hour intervals starting from the time of admission; NEMS8a.m.: 24-hour intervals starting at 8 a.m.).Results: NEMSindividual and NEMS8a.m. were collected on 3236 patient days; 687 patients were involved. Significantly lower scores were found for the NEMS8a.m. (25.0 ± 8.7) compared to the NEMSindividual (26.1 ± 8.9, p <0.01); the interclass correlation coefficient (ICC) was good but not excellent: 0.78. The inter-rater correlation between the two NEMS scores was high or very high (κ = 0.6-1.0) for six out of nine variables of the NEMS.Conclusions: Different sampling strategies produce different score values, especiallydueto the end of stay. This has to betaken into accountwhen using the NEMS in quality assurance projects and multi-center studies.
Keywords: Data management system; computerized patient record; risk score; sampling strategies; TISS score; NEMS